Implementation of Behavioral Counseling Theory with Mechanical Behavior Assertiveness Training in Improving Students to Receive Feedback from Others through Lesson Study in Sukasada - Omegatjefco Delha Ndoen; I Ketut Gading; I Ketut I Ketut Darsana (RedwhitePress)
This study aims to Determine the effectiveness of behavioral counseling in improving the behavior of students receiving advice from others with cognitive-behavioral counseling theory with modeling techniques to improve student behavior. The research was conducted using a sample of 20 students taken from 32 students. Data collection in this study uses a questionnaire. Then the results from the questionnaire were analyzed based on the product moment and t formulas, and it can be concluded that tcount = 4.31 > ttable = 2.02, that Ho is rejected and Ha is accepted. It was concluded that there was effectiveness in counseling using cognitive-behavioral modeling techniques in improving the behavior of students receiving advice from others.